ANGINA PECTORIS TIDAK STABIL (UAP) - Boy Hutaperi; Lidia Dewi (Nusantara Hasana Journal, 2025)
Unstable Angina Pectoris (UAP) is a form of acute coronary syndrome characterized by new-onset chest pain, worsening angina, or symptoms occurring at rest without elevation of cardiac biomarkers. This condition reflects unstable myocardial ischemia and requires prompt management to prevent progression to myocardial infarction. The diagnosis of UAP is established through a combination of clinical symptoms and electrocardiographic findings such as transient ST-segment depression, T-wave inversion, or other ischemic changes, accompanied by normal troponin levels. Initial management includes the administration of antiplatelet agents, anticoagulants, nitrates, beta-blockers, and statins according to current guidelines, along with risk stratification to determine the need for invasive intervention. Further evaluation through coronary angiography is essential to assess the degree of coronary artery stenosis and guide subsequent treatment strategies, whether through percutaneous coronary intervention or intensive medical therapy. Early identification, comprehensive evaluation, and evidence-based intervention are crucial to reducing morbidity and preventing more severe cardiovascular complications in patients with UAP.